An improved method for studying whole sections of late developing wheat grain. (3rd October 2018) - Zhang, R; Li, C; Fu, K; Li, C; Li, C
Abstract: Whole sections are important for investigation in situ of the development of cell morphology and accumulation of storage substance in cereal kernels. We developed an improved, simple method to obtain good quality whole histological sections of wheat grains during mid- and late-stage (28 and 35 days post anthesis) grain filling. The wheat grains were fixed and dehydrated, cleared in chloroform for 3 days and infiltrated in paraffin at 55° C for 3 − 5 days. The infiltrated grains then were embedded in paraffin wax, softened using diethyl pyrocarbonate (DEPC) water before sectioning. After these treatments, the wheat grains can be sectioned easily at 10 − 25 μm while retaining the cellular structure and antigenicity. The cell structure, cell distribution, autofluorescence, starch accumulation and localization in situ of bam1, one of the genes encoding β-amylase transcripts in the sections of the late developing wheat grain were observed readily.